2020
DOI: 10.3390/ani10111951
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MicroRNA Transcriptomes Reveals the Association between MiR-148a-3p Expression and Rumen Development in Goats

Abstract: The rumen is an important digestive organ of ruminants. From the fetal to adult stage, the morphology, structure and function of the rumen change significantly. However, the knowledge of the intrinsic genetic regulation of these changes is still limited. We previously reported a genome-wide expression profile of miRNAs in pre-natal goat rumens. In this study, we combined and analyzed the transcriptomes of rumen miRNAs during pre-natal (E60 and E135) and post-natal (D30 and D150) stages. A total of 66 different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…MiR-148a can negatively regulate cell proliferation, migration, and invasion by downregulating MTA2 in salivary adenoid cystic carcinoma cells (Li et al, 2018 ). In goat rumen, the expression of miR-148a-3p was significantly different between stages, and involved in the development of the rumen epithelial cells by targeting QKI , meanwhile proliferation of GES-1 cells were induced by miR148a-3p inhibitor (Zhong et al, 2020 ). So we hypothesize the stable expression of chi-miR-148a-3p in goat SMGs is also related to the growth and development of SMGs cells, which need further study.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-148a can negatively regulate cell proliferation, migration, and invasion by downregulating MTA2 in salivary adenoid cystic carcinoma cells (Li et al, 2018 ). In goat rumen, the expression of miR-148a-3p was significantly different between stages, and involved in the development of the rumen epithelial cells by targeting QKI , meanwhile proliferation of GES-1 cells were induced by miR148a-3p inhibitor (Zhong et al, 2020 ). So we hypothesize the stable expression of chi-miR-148a-3p in goat SMGs is also related to the growth and development of SMGs cells, which need further study.…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrates are degraded into volatile fatty acids and absorbed by the rumen epithelial cells [ 29 ]. Many studies have reported related gene expression profiles during rumen development in goats [ 24 , 28 , 42 , 43 , 44 ]. To date, few studies have assessed the applicability of HKG standardization in this tissue, and the identification of RGs has not been based on genome-wide identification.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have pointed out the main mechanisms related to the absorption and transport of nutrients, such as passive diffusion [ 21 ], acid anion exchange [ 22 ], proton-coupled volatile fatty acid (VFA) transport [ 23 ], and electrically mediated VFA transport [ 20 ]. Many candidate genes and noncoding RNAs have been investigated to explore their functions during rumen development [ 24 , 25 , 26 , 27 , 28 ]. Therefore, the selection and validation of RGs are necessary prior to assessing the expression levels of candidate genes without bias.…”
Section: Introductionmentioning
confidence: 99%
“…When the expression of let-7f increased, the expression of NDRG3 decreased. Under hypoxic conditions, stable NDRG3 protein could promote angiogenesis and cell growth by activating the Raf-ERK pathway [ 28 ]. The experimental results confirmed the new mechanism of let-7f regulating the expression of NDRG3.…”
Section: Discussionmentioning
confidence: 99%